Role of Pak-China Economic Corridors (CPEC) in promoting Interregional Connectivity between South Asia and Central Asia - Qaddos, Maira; Waheeda, Amna (Annals of Human and Social Sciences, 2023)
CPEC is expected to improve bilateral relations, logistics, infrastructure and connectivity among people of the whole region. Major objective of this paper to explore how CPEC will transform the regions of Central Asia and Southern Asia by doing systematic literature review of available literature in the form of books, journals and research reports etc. Study finds that CPEC will remove trade barriers, improve regional infrastructure and telecommunication networks across the region resulting in financial stability, cultural exchange and government level relationship. However, there are certain reservations of political parties and people about route and benefits of CPEC. Moreover, Iran and India considers it an unacceptable project because India is investing in Iranian port of Chahbahar and emergence of Gwadar as a new trade network will threaten its strategic importance. Study recommends that there is a need to address all the concerns to avoid any hindrance in completion of CPEC.